Facing diversity and democracy: European neo-nationalism, Canadian multiculturalism and Latin American experiences - Campani, Giovanna (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
The paper tries to demonstrate that the debate about cultural diversity cannot avoid issues concerning the historical nature of the European nation-state, the transformations provoked by the creation of the European Union, and the relationship between the nation state and democracy. The European historical specificities mark the forms multiculturalism can take. The paper tries as well to show how multiculturalism policies vary according to the contexts. In a comparative perspective, the paper considers the development of multiculturalism outside Europe, looking in the first place at the Canadian experience, Canada being a pioneer in making of multiculturalism an official policy; then at the Latin American experiences of multiculturalism and of “multinationalism” (Barabas, 2015). In order to clarify how multiculturalism (and multinationalism) was implemented in Latin America, the paper briefly discusses the historical formation of the Latin American states. It finally considers how a comparative Europe/Latin America perspective can be useful to clarify the European dilemmas.